Dialektika Penafsiran Ayat Riba antara Tafsir Al-Jassas dan Tafsir Al-Azhar: Implikasi terhadap Status Bunga Bank - Junaedi Akbar; Desi Cahya Anggraeni (MUAMALAH: Journal of Islamic Economics and Business Law, 2026)
The theological debate regarding the equivalence of riba and bank interest remains a central unresolved issue in Islamic economic law. This study aims to analyze the dialectic interpretation of riba verses between two scholars from different eras and backgrounds: Abu Bakar Al-Jassas in Ahkam al-Qur'an and Buya Hamka in Tafsir Al-Azhar, and its implications for the legal status of contemporary bank interest. Using a qualitative method with a library research approach and comparative analysis (tafsir muqaran), this study dissects the legal deduction methodology of both scholars in formulating the 'illat (legal ratio) of the prohibition of riba. The results indicate a sharp epistemological divergence. Al-Jassas, representing the classical legal-formal paradigm, defines riba textually as any stipulated addition (az-ziyadah al-masyruuthah). Consequently, he views the prohibition as absolute (ta'abbudi) regardless of the loan purpose, rendering bank interest totally forbidden (haram). Conversely, Buya Hamka, representing the modern socio-ethical paradigm, emphasizes injustice (dzulm) and exploitation as the substance of riba. Hamka distinguishes between exploitative consumptive loans and productive banking loans, thus placing state bank interest in the realm of syubhat or permissible due to development emergencies (dharurah). The study concludes that the difference in the legal status of bank interest is rooted in the tension between static text (Al-Jassas) and dynamic context (Hamka). The implication is that while Al-Jassas's conservative view is theologically safer, Hamka's moderation provides a realistic foundation for the economic transition of the Ummah. This study recommends strengthening the Islamic banking system as the final solution to invalidate the emergency argument.